2017
DOI: 10.1002/2017jc012726
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Oceanography in the Tyrrhenian Sea: Thermohaline Staircases, Eddies, and Internal Waves

Abstract: We use seismic oceanography to document and analyze oceanic thermohaline fine structure across the Tyrrhenian Sea. Multichannel seismic (MCS) reflection data were acquired during the MEDiterranean OCcidental survey in April–May 2010. We deployed along‐track expendable bathythermograph probes simultaneous with MCS acquisition. At nearby locations we gathered conductivity‐temperature‐depth data. An autonomous glider survey added in situ measurements of oceanic properties. The seismic reflectivity clearly delinea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 72 publications
0
40
1
Order By: Relevance
“…can have a great impact on the ocean circulation/ecosystem state and evolution through their particular structures and transport mechanisms. Other fine scale processes are clearly involved in the ocean mixing, like microturbulence (Fer et al, 2014;Palmer et al, 2015;Schultze et al, 2017) or frontogenesis, filamentation due to stirring or symmetric instability (Figure 11 and Ruiz et al, 2012;Thompson et al, 2014Thompson et al, , 2016Thomsen et al, 2016;Pietri et al, 2013;Brannigan et al, 2017;Buffett et al, 2017;Du Plessis et al, 2017;Pascual et al, 2017;Kolodziejczyk et al, 2018) that can lead to significant vertical velocities and fluxes. However, the extent and variability of their impact over long periods of time still needs to be assessed.…”
Section: Mesoscale and Submesoscale Phenomenamentioning
confidence: 99%
“…can have a great impact on the ocean circulation/ecosystem state and evolution through their particular structures and transport mechanisms. Other fine scale processes are clearly involved in the ocean mixing, like microturbulence (Fer et al, 2014;Palmer et al, 2015;Schultze et al, 2017) or frontogenesis, filamentation due to stirring or symmetric instability (Figure 11 and Ruiz et al, 2012;Thompson et al, 2014Thompson et al, , 2016Thomsen et al, 2016;Pietri et al, 2013;Brannigan et al, 2017;Buffett et al, 2017;Du Plessis et al, 2017;Pascual et al, 2017;Kolodziejczyk et al, 2018) that can lead to significant vertical velocities and fluxes. However, the extent and variability of their impact over long periods of time still needs to be assessed.…”
Section: Mesoscale and Submesoscale Phenomenamentioning
confidence: 99%
“…Sparnocchia et al (1999) confirmed such extension northwest of Sicily. More recently, high-resolution synoptic observations of staircases by seismic data have been reported along three zonal transects north of the 40 • N parallel (Buffett et al, 2017). The staircases are depicted as continuous stripes, well-ordered in the central part of the basin and weakening close to the continental slope, with remarkable spatial continuity.…”
Section: Areal Extents Delineated By Large-scale Circulation Featuresmentioning
confidence: 99%
“…Thanks to biannual surveys at a higher spatial resolution, the authors reported the different layering aspects: well-ordered vertical structures around 4 • E progressively eroded westwards and jumbled profiles in the eastern stations. More recently, glider surveys along 3 and 4 • E have provided high-resolution synoptic observations of thermohaline staircases with a remarkable structural spatial continuity between the two layering aspects (Cotroneo et al, 2019). These reports are in agreement with the regionalization by staircase regimes proposed by Krahmann (1997): a region of inverted layers close to Sardinia where LIW enter the basin and flow northwards along the continental slope, farther west a region of well-ordered layering and then a westernmost region with "diffusively reduced" layers.…”
Section: Areal Extents Delineated By Large-scale Circulation Featuresmentioning
confidence: 99%
See 2 more Smart Citations